Serological Evidence of Arboviruses in Horses During West Nile Fever Monitoring Surveillance in Southeastern Brazil - Guimarães, Mylenna de Cássia Neves; Freitas, Maria Nazaré Oliveira; Sousa, Alana Watanabe de; Cunha, Marcos Antônio Correia Rodrigues da; Almada, Gilton Luiz; Romano, Alessandro Pecego Martins; Santos, Maria Guadalupe Dias Pestana; Rodrigues, Gilsa Aparecida Pimenta; Martins, Lívia Caricio; Chiang, Jannifer Oliveira; Casseb, Livia Medeiros Neves (Frontiers in Tropical Diseases, 2022)
Many human arboviruses are also pathogenic for horses, and some of these have emerged recently. A descriptive cross-sectional observational study was conducted to assess the prevalence of West Nile virus (WNV) and other arboviruses among 77 horses on the rural properties of the Espirito Santo state, Brazil. Serum samples were screened for arbovirus-reactive antibodies using the hemagglutination inhibition technique and subsequently a plaque reduction neutralization test for the confirmation of exposure from sera was used to detect heterotypic immune reactions. Overall, the total antibodies against at least one arbovirus of Alphavirus, Flavivirus, and Orthobunyavirus genera were detected in 39 (50.6%) animals. The antibodies to Phlebovirus were not detected in any sample. When the 24 WNV hemagglutination inhibition (HI)-positive samples were tested by the plaque-reduction neutralization test 90%, 9 (32.1%) were positive for WNV antibodies and 14 (50%) for Saint Louis encephalitis virus. Our findings indicate that the region provides ideal conditions for the emergence of arboviruses, reinforcing the need for further surveillance of mosquito-transmitted diseases in domestic animals.